Les scénarios énergétiques à l’épreuve du stockage des énergies intermittentes - Fontecave, Marc; Grand, Dominique (Comptes Rendus. Chimie, 2021)
A large share of wind and solar in the electricity mix increases the part of fatal and intermittent productions which must be compensated by a back up system able to continuously equate supply and demand. The goal of the study is the dimension of this back up system. The analysis relies on information from wind and solar productions observed today in France and transposed to two scenarios considered for 2050: one with 100% renewables, the other with 50% renewables and 50% nuclear. For both cases, we compute the volume of electricity, which should be transferred annually by the back up system from times of productions surplus to those of deficits. In this operation, the back up must deliver a power and possess a capacity of storage, which are also evaluated. Knowing these required performances for the back up system, a review is made of its foreseeable constituents: exchanges with neighboring countries, adjustment of consumption, storages (gravitational, electrochemical and chemical) and, last but not least, adjustment of the supply with controlled, carbon-free, production sources (mostly hydroelectric and nuclear plants). At the end, this gives an insight on the realism of the scenarios, the efforts they require, and the uncertainties in their achievement. Even if our results could be modulated by other hypotheses, their main lesson would remain and cannot be disregarded in the conduct of the energy transition.